Gems and gemmology : an introduction for archaeologists, art-historians and conservators /: an introduction for archaeologists, art-historians and conservators. (©2020) - Karampelas, Stefanos; Kiefert, Lore; Bersani, Danilo; Vandenabeele, Peter
No abstract available